2015
DOI: 10.1073/pnas.1517662112
|View full text |Cite
|
Sign up to set email alerts
|

Conservatives negatively evaluate counterstereotypical people to maintain a sense of certainty

Abstract: People frequently use physical appearance stereotypes to categorize individuals when their group membership is not directly observable. Recent research indicates that political conservatives tend to use such stereotypes more than liberals do because they express a greater desire for certainty and order. In the present research, we found that conservatives were also more likely to negatively evaluate and distribute fewer economic resources to people who deviate from the stereotypes of their group. This occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…There is, moreover, mounting evidence that conservatives are quicker to apply group stereotypes and more likely to devalue individuals who deviate from the stereotype, in comparison with liberals (e.g., Stern, West, & Rule, 2015; see also Luguri, Napier, & Dovidio, 2012; Olivola, Sussman, Tsetsos, Kang, & Todorov, 2012). For example, conservatives are more likely than liberals to assume that men with stereotypically feminine facial features—such as long eyelashes, high cheekbones, and slender faces—are gay (Stern, West, Jost, & Rule, 2013).…”
Section: Ideological Differences In Personality Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is, moreover, mounting evidence that conservatives are quicker to apply group stereotypes and more likely to devalue individuals who deviate from the stereotype, in comparison with liberals (e.g., Stern, West, & Rule, 2015; see also Luguri, Napier, & Dovidio, 2012; Olivola, Sussman, Tsetsos, Kang, & Todorov, 2012). For example, conservatives are more likely than liberals to assume that men with stereotypically feminine facial features—such as long eyelashes, high cheekbones, and slender faces—are gay (Stern, West, Jost, & Rule, 2013).…”
Section: Ideological Differences In Personality Characteristicsmentioning
confidence: 99%
“…Stern et al (2015) investigated the hypothesis that conservatives would not only rely more heavily on stereotypes but would also be more likely than liberals to evaluate negatively those individuals who deviate from the stereotype. Thus, in one study they observed that conservatives evaluated masculine‐looking gay men less favorably than feminine‐looking gay men, whereas liberals displayed no differences in evaluation.…”
Section: Ideological Differences In Personality Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the research showing that employment discrimination against gay men is strongest amongst employers searching for applicants with stereotypically masculine traits (Tilcsik, 2011), suggests that discrimination will vary across occupations that are highly gender segregated. Moreover, the research showing that conservatives evaluate counterstereotypical gay men more negatively than stereotypical gay men (Stern, West, & Rule, 2015) suggests that the discrimination observed in this counterstereotypical context (football internship) might not generalize to gay men applying to intern in more stereotype consistent, or stereotype neutral, positions. Future work might also explore more and varied signals to sexual stigma.…”
Section: Discussionmentioning
confidence: 99%
“…One implication of this literature is that conservatives are more likely than liberals to embrace brands, because brands (at least, well managed ones) provide the certainty and predictability that conservatives prefer. Conservatives may even be more forgiving of brands under some conditions: Research on judgments of counterstereotypical targets (Stern, West, & Rule, 2015) implies that a brand with a flaw (versus without) may be preferred, as long as the flaw is congruent with stereotypes of the brand's country of origin or user community.…”
mentioning
confidence: 99%